Recursos hídricos, agroindústrias e desenvolvimento regional na região Oeste do Paraná - Campos, Rafael Flores de (2021)
Regional development is based on productive specialization, in which the abundance of natural resources can be the basis for this process, while the way these resources are managed is the parameter for evaluating symptoms of underdevelopment or development. Still, the growing worldwide awareness about the way natural resources are used has been provoking changes in consumption and production patterns. In Brazil, this pressure has been falling on agribusiness, which, together with agribusinesses, accounts for more than two thirds of the use of water resources in the country. In this sense, agribusinesses characterize the main driving industry of the Western Region of Paraná and have been presenting themselves as a growing sector, however, with a large negative externality, its water footprint. Although Brazil has about 14% of the world's freshwater reserves, forecasts indicate that problems such as lack of water resources will be configured as bottlenecks to the growth of the agribusiness sector. There is a need for the adoption of adequate environmental management postures, in order to achieve positive effects on the environment, reducing, eliminating, or compensating the environmental problems resulting from this activity. In view of this, this study sought to understand the relationship of the agro-industries in Western Paraná with the issue of water resources, evaluating the concern regarding the use of these resources in view of the tendencies of agro-industrial productive expansion, with the purpose of verifying if there is a mismatch as to the environmental approach adopted in the environmental praxis used and the industrial growth strategies. For this, the method of methodological triangulation was chosen, using a documental survey, self-answered questionnaires, and interviews as a source of data. The results showed that by understanding the competitive environment of the global market, the changes in legislation, water shortage situations, consumer behavior and the increase in the sustainability aspect as a competitive differential, it is possible to verify a misalignment regarding the approach adopted in environmental actions and the industrial growth strategies that are expected for organizations in this scenario. Most of the surveyed companies operate in the international market, have been facing situations of lack of water availability, already suffer with restrictions caused by the legal environment and understand that there is pressure from society for a change in behavior regarding environmental issues. In such a way that this vulnerability can compromise the main development mechanism of the Western region of Paraná, showing that the relation between agribusiness and hydric resources needs more attention. Thus, it is important to adopt environmental actions consistent with the scenario that is configured for these resources, since the identification of differentials and weaknesses in regional development studies contributes to the process of modification of the territory. This repositioning occurs with the environmental maturity of the organization, as it sees the environmental function as intrinsic to the productive and administrative function.